2010
DOI: 10.1177/0734242x10387312
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of organic wastes through composting for land applications: a Nigerian experience

Abstract: In-vessel composting, a contribution to sustainable solid waste management, was conducted on source-separated waste materials generated in Abeokuta city, south-west Nigeria. Feedstock (household, agricultural and municipal waste) and the resultant composts were chemically characterized using standard procedures. Identification and changes in the microbial population during composting, the effects of composting on waste volume reduction (WVR) and elemental composition of composts were evaluated. Product perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 17 publications
4
19
0
Order By: Relevance
“…Municipal Solid Waste Management (MSWM) is a globally challenging issue especially in developing countries, due to its adverse environmental effects [12][13][14]. Solid waste management has emerged as one of the greatest challenges facing federal state and local government environmental protection agencies in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Municipal Solid Waste Management (MSWM) is a globally challenging issue especially in developing countries, due to its adverse environmental effects [12][13][14]. Solid waste management has emerged as one of the greatest challenges facing federal state and local government environmental protection agencies in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…"Al Sabahi et al [11] reported that toxic or contaminable leachates from municipal solid wastes dumpsites could be transformed physically, chemically or biologically, and transported via the air, or through runoffs which can contaminate the soil, surface or groundwater [12][13]". Also, toxic fumes and greenhouse gases are also being produced by precarious or uncontrolled in-situ burning [14], which could have acute or chronic health and environmental consequences [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…[13] posited that waste management is a serious concern due to its human health and environmental sustainability implications. To corroborate this assertion various authors have opined that waste management is a globally challenging issue faced by mankind for decades [14][15][16]. It implies that environmental pollution, on global, regional and local scales should be of primary concern for humanity in the modern era and the future.…”
Section: Introductionmentioning
confidence: 99%